PENGARUH METODE SILABA BERBANTUAN MEDIA BIG BOOK TERHADAP KEMAMPUAN MEMBACA PERMULAAN KELAS 1 SEKOLAH DASAR - Venti Vernanda; Bahauddin Azmy (LPPM Universitas Cipta Mandiri, 2024)
The poor beginning reading abilities of first graders, who face multiple problems, were the driving force behind the study. Even now, some of them are still stuttering and some don't know the alphabet. The aim of this study is to find out whether the silaba method with the help of Big Book media has an impact on the beginning reading ability of class I students at SDN Keboananom Gedangan. By using a Posttest-Only Control Design, this research design is quasi-experimental. Those participating in this research were all students at SDN Keboananom Gedangan in classes I A and I B. The experimental class was class I B, and all students in class I A were the control group. A test, Posttest, is used to carry out data collection techniques. Based on a study entitled